Introduction of SARS-CoV-2 variant of concern 20h/501Y.V2 (B.1.351) from Malawi to Italy. Issue 1 (1st January 2021) - Novazzi, Federica; Genoni, Angelo; Spezia, Pietro Giorgio; Focosi, Daniele; Zago, Cristian; Colombo, Alberto; Cassani, Gianluca; Pasciuta, Renee; Tamborini, Antonio; Rossi, Agostino; Prestia, Martina; Capuano, Riccardo; et al.
ABSTRACT: We report here an imported case of SARS-CoV-2 variant of concern B.1.1.351 (also known as 20H/501Y.V2 or "South African variant" or VOC 202012/02) in a 66-years old symptomatic male who returned from Malawi to Italy.